Eksplorasi Etnomatematika Pada Makan Khas Tegal Sebagai Sumber Literasi dan Sumber Belajar Matematika - Kusuma Ningtyas Pramita Resya; Ikhda Nurnoviyati (Jurnal Ilmiah Wahana Pendidikan, 2022)
Culture-based mathematics is often called ethnomathematics. Ethnomathematics is an approach to explain the role of mathematics in a multicultural society so that it is more meaningful. Every culture can be used as a source of learning and literacy for students to learn mathematics where in each culture there are values ​​that are important in life. Where in teaching geometry to elementary school students really need media to visualize geometric shapes and geometric shapes. This research is very useful for teachers and students in elementary schools, because it can help students understand and also make it easier for teachers to explain geometry material to their students. The method used in this research is a literature study, namely reviewing relevant previous studies and making conclusions based on the results obtained. The results of this study are the concept of the shape of each typical Tegal food, namely latopia cake, tofu aci, olos, pestle, bogis poci, kamir and apem typical of Tegal, which have been described can be used as alternative learning resources related to the discussion of flat geometry. and geometry of space as well as other relevant things to learn related to mathematics